2012
DOI: 10.1097/smj.0b013e31824e1737
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Abnormalities in Hospitalized Patients

Abstract: Depending upon the method of measurement, hypocalcemia occurs in 15% to 88% and hypercalcemia occurs in 15% of hospitalized patients. Ionized calcium should be measured in place of total serum calcium to avoid errors related to hypoalbuminemia, which is seen commonly in acutely ill patients. Symptomatic hypocalcemia requires prompt intravenous calcium administration. Symptomatic hypercalcemia (most often caused by hyperparathyroidism or malignancy) warrants aggressive intravenous hydration to correct volume de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 75 publications
0
15
0
2
Order By: Relevance
“…The goals of therapy should include returning the serum [P] to normal (eg, 2.7-4.5 mg/dL [~0.9-1.45 mmol/L]), avoiding or resolving symptoms of hyperphosphatemia, and possibly maintaining the serum Ca-P product <55 mg 2 /dL 2 . 40,85,86 Hypocalcemia Hypocalcemia (total serum [Ca] <8.6 mg/dL [~2.15 mmol/L], ionized [Ca] <1.1 mmol/L) has been reported in approximately 15%-88% of hospitalized adult patients, 90 and one study observed hypocalcemia in approximately 21% of critically ill trauma patients. 25 Hypocalcemia is often associated with hypoalbuminemia in hospitalized patients, but other causes can include sepsis, pancreatitis, renal insufficiency, hypoparathyroidism, administration of blood preserved with citrate, hypomagnesaemia, and hyperphosphatemia.…”
Section: Hyperphosphatemiamentioning
confidence: 98%
See 1 more Smart Citation
“…The goals of therapy should include returning the serum [P] to normal (eg, 2.7-4.5 mg/dL [~0.9-1.45 mmol/L]), avoiding or resolving symptoms of hyperphosphatemia, and possibly maintaining the serum Ca-P product <55 mg 2 /dL 2 . 40,85,86 Hypocalcemia Hypocalcemia (total serum [Ca] <8.6 mg/dL [~2.15 mmol/L], ionized [Ca] <1.1 mmol/L) has been reported in approximately 15%-88% of hospitalized adult patients, 90 and one study observed hypocalcemia in approximately 21% of critically ill trauma patients. 25 Hypocalcemia is often associated with hypoalbuminemia in hospitalized patients, but other causes can include sepsis, pancreatitis, renal insufficiency, hypoparathyroidism, administration of blood preserved with citrate, hypomagnesaemia, and hyperphosphatemia.…”
Section: Hyperphosphatemiamentioning
confidence: 98%
“…2,24 Magnesium deficiency may impair PTH release and/or activity and contribute to hypocalcemia. 4,[90][91][92] The hallmark sign of severe acute hypocalcemia is tetany, but other neuromuscular, cardiovascular, and central nervous [93][94][95][96] It would be prudent to establish a standardized method for ordering Ca supplementation to minimize the risk of errors. [97][98][99] This approach should include using Ca gluconate as the preferred salt for routine Ca maintenance dosing and supplementation and restricting Ca chloride for use in urgent and emergent situations.…”
Section: Hyperphosphatemiamentioning
confidence: 99%
“…As with the current case, treatment with saline solution may suffice for correcting hypercalcemia along with treatment of the underlying etiological factors without further medication (2,3). However, such therapeutic modalities as loop diuretics, biphosphonates, calcitonin, glucocorticoids, and hemodialysis should be added in the patents not responding to effective hydration.…”
Section: Resultsmentioning
confidence: 99%
“…Hypercalcemia is a laboratory finding of a wide variety of conditions. Primary hyperparathyroidism (50%) and hypercalcemia associated with malignancies (30-40%) constitute about 90% of all hypercalcemias (2,3). The remaining 10% of hypercalcemias are caused by granulomatous diseases, several drugs (thiazide diuretics, lithium, vitamins D and A, aluminum intoxication), endocrine disorders such as thyrotoxicosis, pheochromocytoma, and adrenal insufficiency, and other rarer diseases like familial hypocalciuric hypercalcemia (2).…”
Section: Introductionmentioning
confidence: 99%
“…Among the major causes of hypocalcemia, only vitamin D deficiency emerged. [13][14][15] Regarding other possible causes of hypocalcemia, our patient never received diuretic therapy; massive intestinal loss of electrolytes was excluded because Emilia had occasional constipation, which she resolved taking small amounts of herbal products; anti-transglutaminase antibodies were absent. She never presented pancreas nor kidney disease except a slightly increase in urinary protein excretion, and phosphatemia was normal.…”
Section: Discussionmentioning
confidence: 99%